In vitro Activity of Antivirulence Drugs Targeting the las or pqs Quorum Sensing Against Cystic Fibrosis Pseudomonas aeruginosa Isolates - Collalto, Diletta; Giallonardi, Giulia; Fortuna, Alessandra; Meneghini, Carlo; Fiscarelli, Ersilia; Visca, Paolo; Imperi, Francesco; Rampioni, Giordano; Leoni, Livia (Frontiers in Microbiology, 2022)
The chronic lung infection caused by Pseudomonas aeruginosa is a major cause of morbidity and mortality in cystic fibrosis (CF) patients. Antivirulence drugs targeting P. aeruginosa quorum sensing (QS) systems are intensively studied as antibiotics substitutes or adjuvants. Previous studies, carried out in non-CF P. aeruginosa reference strains, showed that the old drugs niclosamide and clofoctol could be successfully repurposed as antivirulence drugs targeting the las and pqs QS systems, respectively. However, frequent emergence of QS-defective mutants in the CF lung undermines the use of QS inhibitors in CF therapy. Here, QS signal production and susceptibility to niclosamide and clofoctol have been investigated in 100 P. aeruginosa CF isolates, with the aim of broadening current knowledge on the potential of anti-QS compounds in CF therapy. Results showed that 85%, 78% and 69% of the CF isolates from our collection were proficient for the pqs, rhl and las QS systems, respectively. The ability of both niclosamide and clofoctol to inhibit QS and virulence in vitro was highly variable and strain-dependent. Niclosamide showed an overall low range of activity and its negative effect on las signal production did not correlate with a decreased production of virulence factors. On the other hand, clofoctol displayed a broader QS inhibitory effect in CF isolates, with consequent reduction of the pqs-controlled virulence factor pyocyanin. Overall, this study highlights the importance of testing new antivirulence drugs against large panels of P. aeruginosa CF clinical isolates before proceeding to further pre-clinical studies and corroborates previous evidence that strains naturally resistant to QS inhibitors occur among CF isolates. However, it is also shown that resistance to pqs inhibitors is less frequent than resistance to las inhibitors, thus supporting the development of pqs inhibitors for antivirulence therapy in CF.